Studi Tokoh Filsafat Kontemporer Alfred North Whitehead 1861-1974 - Al Zikri Suwalam; Maulida Rahmi Lubis; Rahmi; Mardhiah Abbas (Yayasan Bayt Shufiya Nusantara, 2026)
This study aims to describe the philosophical thought of Alfred North Whitehead, a prominent figure in contemporary philosophy, employing the method of biographical study of thinkers. Alfred North Whitehead (1861–1947), an English mathematician and philosopher, is renowned for his theory of “process philosophy.” The core elements of his thought emphasize that reality is not static but is constituted by processes of “becoming,” actual entities, and universal interconnectedness. The implications of his ideas have significantly influenced fields such as metaphysics, theology, ethics, and ecology. The rationale for this research lies in the ongoing relevance of Whitehead's concepts for the development of contemporary philosophy. The findings reveal that Whitehead's thought offers an alternative paradigm that is highly contextual. In conclusion, his contributions enrich the understanding of contemporary reality.